Computer-Based Auditory Training Programs for Children with Hearing Impairment – A Scoping Review - Nanjundaswamy, Manohar; Prabhu, Prashanth; Rajanna, Revathi Kittur; Ningegowda, Raghavendra Gulaganji; Sharma, Madhuri (International Archives of Otorhinolaryngology, 2018)
Introduction Communication breakdown, a consequence of hearing impairment (HI), is being fought by fitting amplification devices and providing auditory training since the inception of audiology. The advances in both audiology and rehabilitation programs have led to the advent of computer-based auditory training programs (CBATPs).Objective To review the existing literature documenting the evidence-based CBATPs for children with HIs. Since there was only one such article, we also chose to review the commercially available CBATPs for children with HI. The strengths and weaknesses of the existing literature were reviewed in order to improve further researches.Data Synthesis Google Scholar and PubMed databases were searched using various combinations of keywords. The participant, intervention, control, outcome and study design (PICOS) criteria were used for the inclusion of articles. Out of 124 article abstracts reviewed, 5 studies were shortlisted for detailed reading. One among them satisfied all the criteria, and was taken for review. The commercially available programs were chosen based on an extensive search in Google. The reviewed article was well-structured, with appropriate outcomes. The commercially available programs cover many aspects of the auditory training through a wide range of stimuli and activities.Conclusions There is a dire need for extensive research to be performed in the field of CBATPs to establish their efficacy, also to establish them as evidence-based practices.
Keywords: auditory training; computer-based; auditory rehabilitation; software